KEBIJAKAN PEMERINTAH TENTANG PENURUNAN TINGKAT PENGANGGURAN DI KOTA MANADO - Lelau, Alfred (Universitas Sam Ratulangi, 2013)
Indonesia as a developing country to this day still cannot be separated from the social problems that gripped the community, especially the socio-economic problems and the problems this government works. For field play an important role in order to protect its people from all socio-economic problems worse excesses, life in society a reality if in the absence of the role of government, the people will give birth to various forms of violence and chaos. The most frightening Scourge of the impact of socio-economic problems is unemployment. Employment issues in Indonesia today has reached a very alarming condition Characterized by the number of unemployed and underemployed large, relatively low incomes and uneven. If the problem is allowed to continue, this will be a